An overview of plant responses to the drought stress at morphological, physiological and biochemical levels - Wach, Damian; Skowron, Piotr (Polish Journal of Agronomy, 2022)
Agricultural production is continuously constrained by number of biotic and abiotic stresses. Among all, water defi- cit is one of the major abiotic stresses, which adversely affects crop growth and productivity. Drought impairs normal growth, reduces leaf expansion, stem extension and root proliferation, disrupts water relation and water use efficiency. It interferes with the synthesis of photosynthetic pigments, resulting in the decline of light harvesting, generation of reducing power, and reduction of gas exchange and carbon fixation, which in turn, leads to the decline in plant growth and productivity water relations and re- duces water-use efficiency in plants and it finally leads to biomass and final yield reduction of crop plants. However, plants develop some mechanisms of drought tolerance, avoidance or escape. This review presents some aspects of changes in plant at morpho- logical, physiological and biochemical levels induced by drought.